SIGNIFICANCE OF UNITY OF LINGUISTIC LEVELS FOR TEXT COMPREHENSION - Kemertelidze, Nino; Koroshinadze, Liana (European Scientific Journal, ESJ, 2014)
The presented article aims at ascertaining the importance of unity of all linguistic levels for comprehensive understanding of a text. Our research is based on analyzing tropes on different levels taking into consideration broad context as this latter plays the utmost essential role in grasping the main idea of any kind of literary work. The article tries to reveal the particular stages of the mechanism where all levels are synthesized. The highest level of synthesis, where a writer’s world outlook and world image are involved, comprises morphological, syntactic, lexical, semantic, stylistic, symbolic and metasemiotic levels, i.e. all linguistic data. Analysis of all these levels are necessary for full comprehension of an utterance or a text, but if taken separately, neither of them is enough. The most important statement is that full and exhaustive understanding of a text can be reached by a deep dialogue between a writer and a reader where their functions are interchangeable.